2022
DOI: 10.1037/adb0000801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress, alcohol prime dose, and sex on ad libitum drinking.

Abstract: Objective: The Self-Medication Hypothesis (SMH) theorizes that alcohol is used to alleviate negative states. We assessed whether an acute social stressor (Trier Social Stress Test, TSST), a priming dose of alcohol, and participant sex impacted 90-min ad libitum drinking. We expected exposure to stress to be associated with increased consumption, and this effect to be stronger following an alcohol priming dose; we also explored whether participant sex moderated these effects. Method: Using a 2×2 experimental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…This association is important because it expands our current understanding of the proposed internalizing and externalizing pathways [ 3 , 90 , 91 , 92 ] to alcohol-use disorders. The risks associated with the development of internalizing symptoms in early childhood [ 90 , 91 , 92 ], when joined with the risks related to IC in college-aged students [ 16 , 17 , 59 , 60 , 61 , 63 ], creates a subset of college-aged students who are especially vulnerable to suffering alcohol-related consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is important because it expands our current understanding of the proposed internalizing and externalizing pathways [ 3 , 90 , 91 , 92 ] to alcohol-use disorders. The risks associated with the development of internalizing symptoms in early childhood [ 90 , 91 , 92 ], when joined with the risks related to IC in college-aged students [ 16 , 17 , 59 , 60 , 61 , 63 ], creates a subset of college-aged students who are especially vulnerable to suffering alcohol-related consequences.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Leeman et al [ 58 ] found that IC explained the growth in alcohol consequences over three years later. Moreover, behavioral impaired control (i.e., drinking beyond heavy episodic levels despite incentives to limit consumption during ad libitum) causally followed an acute stressor (i.e., Trier Social Stress Test) in a self-administration study [ 59 ]. Clearly, impaired control is a critical risk factor for developing AUDs, particularly among adolescents and young adults [ 17 , 59 , 60 , 61 , 62 , 63 ], yet it is understudied as a construct compared to impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their roles in addiction, the CEA and BLA are validated to regulate responses to anxiety and fear (39, 4648). Recent work suggests that women are more likely to drink to cope with stress and anxiety as compared to men (49), and women who experience social stress reach higher BECs in a subsequent open access drinking test as compared to men (50). Though the current protocol did not measure cortisol levels or conduct any anxiety assays, the recruitment of many amygdala brain regions as hubs in female alcohol binge drinkers, but not males, raises the hypothesis that female C57BL/6J binge drinking may in part be driven by anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Although it sounds quite similar to addictive consumption, the parameters are quite different. Addictive consumption can be described as an inability to stop using a substance or engaging in a behaviour even though it is causing psychological and physical harm (5). The keyword here is 'inability to stop'.…”
Section: The Dark Side Of Consumer Behaviourmentioning
confidence: 99%